2021
DOI: 10.24275/rmiq/ia2271
|View full text |Cite
|
Sign up to set email alerts
|

Motor oil wastewater treatment in a packed bed bioreactor using immobilized native microbial consortium

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…For decades, research has been performed on the different water treatment techniques to measure their efficiency (Asfaha et al, 2021); at that time, it has been identified that these techniques do not have sufficient robustness to eliminate the total of components found in the wastewater matrix (Bazrafshan et al, 2016), also considering petroleum derivatives (Almeida et al, 2019) and oil motor additives (Houbron et al, 2021) as pollutants hard to remove.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, research has been performed on the different water treatment techniques to measure their efficiency (Asfaha et al, 2021); at that time, it has been identified that these techniques do not have sufficient robustness to eliminate the total of components found in the wastewater matrix (Bazrafshan et al, 2016), also considering petroleum derivatives (Almeida et al, 2019) and oil motor additives (Houbron et al, 2021) as pollutants hard to remove.…”
Section: Introductionmentioning
confidence: 99%
“…The microbial degradation of monoaromatic hydrocarbons such as BTEX (benzene, toluene, ethylbenzene, and xylenes) has been extensively reported (Bacosa et al, 2011). AHs seriously threaten our environment by damaging ecosystems and affecting human health when they are accidentally released during exploration, drilling, extraction, storage, refining, and transportation (Houbron et al, 2021;Tao et al, 2020;Vázquez-Vélez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods for the treatment or recovery of waste oil. Up to now, a wide range of treatment techniques such as acids followed by treatment with clay earth (Abu-Elella et al, 2015), regeneration (pretreatment, metal removal by dilution in xylene, & a finishing treatment by passage through the bentonite and a filtration) (Danane et al, 2014), packed bed bioreactor using immobilized native microbial consortium (Houbron et al, 2021), ozonation (Semenova & Patrakov, 2019), and continuous multistage froth flotation (Kanokkarn et al, 2016) have been applied to remove waste motor oils from the environment; however, both their high financial costs and operational difficulties have limited their use on a large scale. The development of new and effective adsorbents involving surface modification has been an important issue recently.…”
Section: Introductionmentioning
confidence: 99%